DIAGNOSTIC MODEL OF COMPUTER SCIENCE TEACHER’S READINESS TO USE VISUALIZATION TECHNOLOGIES - Bakytbekova, Ж.Б.; Pak, Н.И. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The study developed a diagnostic model of computer science teachers' readiness to use visualization technologies in educational practice. The model covers three key components: subject, methodological and managerial, which are interconnected and determine the level of professional training. For each component, readiness levels (low, medium, high) are identified, which allows for a systematic assessment of teachers' competencies. The methods used include theoretical analysis, criteria-based assessment and mathematical calculations to compare the dynamics of teachers' readiness. The results of the study demonstrate that the proposed model provides accurate diagnostics and support in improving the professional training of teachers. The use of this model contributes to the development of digital competence and increased efficiency of the educational process. The developed assessment system is significant for educational science, as it integrates modern approaches to visualization and learning, creating conditions for teachers to adapt to the requirements of the digital environment. The model is designed to conduct assessment procedures for the quality of teachers' professional training.